Dokazi o uporabi ortoz za bolnike po možganski kapi in njihova oskrba v Sloveniji - Goljar, Nika (Rehabilitacija (Ljubljana), 2019)
A common approach to managing lower-limb motor impairments resulting from a stroke is to use an orthotic device, mainly an ankle orthosis (AO) or an ankle-foot orthosis (AFO), to provide direct control of the ankle and foot and facilitate the swing phase of gait. AOs and AFOs have a favourable impact on walking speed, walking impairment (step/stride length), and balance (weight distribution in standing) in stroke patients. The contemporary stroke rehabilitation guidelines therefore recommend that AFOs should be used for ankle instability or dorsiflexor weakness and to improve walking ability and safety. The manuscript presents AOs and AFOs that are available on the Slovenian market, and some of our findings regarding the effects of the use of AOs and AFOs in stroke patients.
Keywords: ankle orthosis; ankle-foot orthosis; evidence based rehabilitation; možganska kap; Orthotic Devices; ortoze za gleženj; ortoze za gleženj in stopalo; rehabilitation; Slovenia; Slovenija; Stroke; z dokazi podprta rehabilitacija